Friction, mechanical and ageing properties of surface modified materials for space debris capture. Issue 5 (1st March 2016) - Ferraris, S.; Perero, S.; Gautier di Confiengo, G.; Chiesa, A.; Messidoro, A.; Ferraris, M.
Highlights: An innovative system for space debris removal is described in the paper. Inorganic/organic surface modifications are proposed for improving capture efficiency of the system. Coefficients of friction of bare/modified materials are monitored for capture efficiency evaluation. Mechanical and ageing characterizations of bare/modified materials are reported. Abstract: Space debris removal is a challenging problem for a clean and safe space environment. The present paper focuses on a novel concept of capture mechanism in the framework of technologies, strategies and concepts known as "tentacles with belts" method. Within this framework two different strategies (based on inorganic or organic materials) have been developed in order to improve the capture efficiency of the belts. The mechanical, tribological and ageing characterization of modified belt fabrics for space application is reported and discussed.